Bi-Directional Position and Speed Estimation Algorithm for Sensorless Control of BLDC Motor - Astik, Mitesh B.; Bhatt, Praghnesh; Bhalja, Bhavesh R. (Electrical, Control and Communication Engineering, 2018)
The observer design for estimation of back EMF to control the Brushless DC (BLDC) motor is proposed in this paper. Rotor position of the BLDC motor is estimated using the sequence of estimated back EMF. During speed reversal of motor, the actual and estimated values of speed fail to track the reference speed and if corrective action is not taken by the observer, the motor goes into the unstable region. To overcome this problem, the speed estimation algorithm is proposed for BLDC motor control during its speed reversal operation. Infinite Impulse Response (IIR) Butterworth first order low-pass filters are used in the observer for smoothing the estimated back EMFs of the BLDC motor. A new controller scheme based on Modified Hybrid Fuzzy PI (MHFPI) controller is proposed to control the speed of the BLDC motor. The effectiveness of the proposed method has been validated through simulations for different disturbances such as step changes in the reference speed and load torque of the motor and results are compared with the existing methods.